An Emergency Energy Management for AC/DC Micro-grids in Industrial Park. Issue 28 (2018) - Miao, Miao; Li, Yong; Wang, Ziya; Ouyang, Li; Liu, Fang; Lee, Kwang Y.; Tan, Yi
Abstract: Industrial parks have the trend to be designed to operate as microgrids with renewable distributed generations and battery storage. In this paper, an energy management system is proposed for AC/DC microgrids. This paper introduces a mixed-integer nonlinear programming method to realize the multiple objectives of emergency energy management. Combined with the comprehensive consideration of the amount of load supply, the cost of power generation and the utilization of battery storage, as well as the number of the switch operation, this paper establishes a composite objective function by synthetically evaluating several criteria. Then, examples are given to illustrate the effectiveness of the proposed method by considering the islanded mode with a generator fault.